2003
DOI: 10.1111/1467-9566.00365
|View full text |Cite
|
Sign up to set email alerts
|

‘About a year before the breakdown I was having symptoms’: sadness, pathology and the Australian newspaper media

Abstract: Portrayals of mental illness in the media reportedly highlight violence and crime by the 'mentally ill'. Using a discourse analytic approach we investigated representations of 'depression' in the print media in Australia during the year 2000. Unlike other 'mental illnesses', in the case of depression the media stress the need for the protection of the sufferer, rather than others. Three key discourses are identified -the biomedical, the psycho-social and the administrative/managerial -which work to normalise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 16 publications
4
46
0
1
Order By: Relevance
“…Especially experts such as health scientists but also health professionals such as medical doctors are shown to be the chosen sources. Journalists also routinely search medical and scientific journals for story ideas and information (Len-Rios et al, 2009;Rowe et al, 2003;Van Trigt et al, 1994). Several authors find an explanation for this finding in the often complex and technical matter of health news.…”
Section: Sourcing Practices In Health News: An Old or New Story?mentioning
confidence: 99%
See 2 more Smart Citations
“…Especially experts such as health scientists but also health professionals such as medical doctors are shown to be the chosen sources. Journalists also routinely search medical and scientific journals for story ideas and information (Len-Rios et al, 2009;Rowe et al, 2003;Van Trigt et al, 1994). Several authors find an explanation for this finding in the often complex and technical matter of health news.…”
Section: Sourcing Practices In Health News: An Old or New Story?mentioning
confidence: 99%
“…Several authors find an explanation for this finding in the often complex and technical matter of health news. Combined with the fact that specialized journalists are increasingly replaced with generalists who have no or limited expertise in the matter, it is not a very big surprise that journalists often turn to experts on the matter for clarification and contextualization (Berkowitz, 1990;Gans, 1979;Holton, 2013;Rowe et al, 2003). "Journalists use expert sources in health stories to provide perspective, contribute balance to the story, discuss research implications, and legitimize other research" (Len-Rios et al, 2009, p.318).…”
Section: Sourcing Practices In Health News: An Old or New Story?mentioning
confidence: 99%
See 1 more Smart Citation
“…What is perhaps more significant about the use of the two repertoires is the way that both of them represent families as in need of interventions, either medical or in the form of advice on parenting and the organisation of family life. Following a Foucauldian rationale, Rowe et al (2003) has suggested that biological and psychosocial repertoires do not actually compete in a broader sense as they can both be drawn on to indicate what parents and families should be like and to give advice on how they should regulate themselves along those lines. Rafalovich (2001: 373) has also argued that parenting guides on ADHD are 'manuals' that are designed to work as 'disciplinary mechanisms' in the domestic environment (c.f.…”
Section: When Is a Child A Problem Child? When Is A Child Suffering Fmentioning
confidence: 99%
“…É inegável a contribuição que conglomerados de comunicação podem dar para a saúde publica e coletiva, ao, por exemplo, colocarem em pauta temas sobre saúde e informar a população sobre os cuidados preventivos. [16][17][18][19][20][21] Rádio, TV e jornal impresso conseguem, através de estratégias de texto e abordagens e abrangências, traduzir as informações e preocupações dos setores públicos, de epidemiologistas e outros profissionais para a população no geral e conseguem assim, responder também as principais dúvidas da população em geral.…”
Section: Jornalismo E Saúdeunclassified